Constraints on the Implementing of Lease Scheme on Land Acquisition in Toll Road Development Investment (E-Jurnal Akuntansi, 2026)
This study aims to determine the constraints faced by the Government of Indonesia in implementing the lease scheme in the land acquisition process in the context of implementing investment in the construction of the Yogyakarta-Bawen toll road. The data used are primary data derived from semi-structured interviews with the Directorate General of Highways of the Ministry of Public Works and Public Housing (PUPR) and secondary data in the form of supporting documents. The data were analyzed using content analysis. The main results show that the constraints faced in the implementation of the lease scheme are the need for a process and time to negotiate towards a lease scheme agreement, the level of financial capability of the Toll Road Business Entity to pay rent, and the absence of regulations governing land leasing for development for the public interest. This study also uses the theory of equality where in this case, with the challenges faced, the lease scheme will be applied in a specific case and cannot be applied generally.
Keywords: Lease; Investment; Toll Road